PENGARUH KEMANDIRIAN BELAJAR DAN GAYA KOGNITIF TERHADAP HASIL BELAJAR IPS SISWA KELAS VII SMP NEGERI SINGKAWANG - Rizqi Alghofiqi; Etin Solihatin; Yufiarti (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of learning independence and cognitive style on social studies learning outcomes for seventh grade students of Singkawang State Junior High School. This research was conducted on seventh grade students of public junior high school in Singkawang city, West Kalimantan. The time of the research was carried out in the odd first semester of the 2021/2022 academic year. This study uses a survey method with a regression approach. Data collection techniques used are indirect communication techniques for learning independence data as well as cognitive style and documentation for student social studies learning outcomes data. As for knowing the effect of learning independence and cognitive style on student learning outcomes, simple linear regression formulas and multiple regressions using the computerized program SPSS 16.0 will be used. By using this SPSS, the results of data analysis stated that there was an influence between learning independence and cognitive style on student learning outcomes of 0.765 (R) with R Square of 0.575 which was determined by the formula KD = R2 x 100% (KD = 0.575 x 100%) to 57.5%, while 42.5% was influenced by other factors not discussed in this study. And in this study, the level of influence was found to be sufficient.